Purification Method and Storage of Primordial Germ Cells-Circulation for Preservation of Local Chicken - Kostaman, Tatan (Indonesian Bulletin of Animal and Veterinary Sciences, 2014)
Primordial germ cells (PGCs) can be used for producing transgenic chickens and preserving genetic material of avian species. Primordial germ cells are precursor of germline cells that could be made proliferation and differentiation to become spermatogonia in testes or oogonia in ovary. Primordial germ cells has a unique migration path, so that the PGCs can be isolated and collected from embryos and propagated and developed through the culture. This paper describes the isolation, collection, purification, storage and transfer of PGCs-circulation of local chickens in Indonesia. Some amount of PGCs-circulation were collected from Gaok chicken at stage 15 as the safe level using cryoprotectant DMSO and some chicks hatched after transfering the PGCs-circulation to recipient embryo. Thus, this technology would be useful for preservation of Indonesian local chicken. Key words: Local chicken, primordial germ cells, cryopreservation